Intersectin 1 Enhances Cbl Ubiquitylation of Epidermal Growth Factor Receptor through Regulation of Sprouty2-Cbl Interaction - Okur, Mustafa Nazir (American Society for Microbiology, 2012)
Ubiquitylation of receptor tyrosine kinases plays a critical role in regulating the trafficking and lysosomal degradation of these important signaling molecules. We identified the multidomain scaffolding protein intersectin 1 (ITSN1) as an important regulator of this process (N. P. Martin et al., Mol. Pharmacol. 70:1463–1653, 2006) ITSN1 stimulates ubiquitylation of the epidermal growth factor receptor (EGFR) through enhancing the activity of the Cbl E3 ubiquitin ligase. However, the precise mechanism through which ITSN1 enhances Cbl activity was unclear. In this study, we found that ITSN1 enhances Cbl activity through disrupting the interaction of Cbl with the Sprouty2 (Spry2) inhibitory protein. We demonstrate that ITSN1 binds Pro-rich regions in both Cbl and Spry2 and that interaction of ITSN1 with Spry2 disrupts Spry2-Cbl interaction, resulting in enhanced ubiquitylation of the EGFR. Disruption of ITSN1 binding to Spry2 through point mutation of the Pro-rich ITSN1 binding site in Spry2 results in enhanced Cbl-Spry2 interaction and inhibition of receptor ubiquitylation. This study demonstrates that ITSN1 enhances Cbl activity by modulating the interaction of Cbl with Spry2. In addition, our results reveal a new level of complexity in the regulation of Cbl through the interaction with ITSN1 and Spry2.